2016
DOI: 10.1016/j.placenta.2015.10.020
|View full text |Cite|
|
Sign up to set email alerts
|

Acute atherosis in vacuum suction biopsies of decidua basalis: An evidence based research definition

Abstract: Our evidence based criterion for decidua basalis AA diagnosis in vacuum suction biopsies may not apply to myometrial or decidua parietalis arteries. In decidual basalis samples it should facilitate comparisons between research studies, to improve pathophysiological understanding of AA and preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 76 publications
4
57
0
2
Order By: Relevance
“…However, the relation between placental bed pathology, the presence or absence of underlying cardiovascular risk factors, and the risk of incident CVD events later in life is not clear. Further, it should be noted that the presence of acute atherosis lesions in the decidua is estimated to occur in about 11% uncomplicated pregnancies [40]. In the study by Harsem et al [14] no associations were found between decidual atherosis lesions and antepartum lipid levels in N ¼ 17 preeclampsia patients.…”
Section: Spiral Arteries and Cardiovascular Riskmentioning
confidence: 89%
“…However, the relation between placental bed pathology, the presence or absence of underlying cardiovascular risk factors, and the risk of incident CVD events later in life is not clear. Further, it should be noted that the presence of acute atherosis lesions in the decidua is estimated to occur in about 11% uncomplicated pregnancies [40]. In the study by Harsem et al [14] no associations were found between decidual atherosis lesions and antepartum lipid levels in N ¼ 17 preeclampsia patients.…”
Section: Spiral Arteries and Cardiovascular Riskmentioning
confidence: 89%
“…Important strengths of our study are the clinically well-defined study population, the constant method of biological sample collection and storage, as well as targeted decidua basalis tissue sampling and thoroughly defined criteria for decidua basalis acute atherosis (Alnaes-Katjavivi et al, 2016). Another advantage is the sophisticated bioassay approach to identify AT1-AA, based on spontaneously beating neonatal rat cardiomyocytes exposed to serum from the pregnant women, where the exact binding site of the AT1-AA to the AT1R is identified.…”
Section: Discussionmentioning
confidence: 99%
“…The decidual tissue acute atherosis diagnosis of the included patients has been performed and published previously for a larger cohort (Alnaes-Katjavivi et al, 2016). In brief, vacuum suction collected and rinsed decidual tissue (endometrium of pregnancy) was formalin fixed, routinely processed and paraffin embedded and used for immunohistochemistry.…”
Section: Evaluation Of Decidua Basalis Tissue For the Presence Of Acumentioning
confidence: 99%
See 1 more Smart Citation
“…Acute atherosis has been described in the spiral arteries of the decidua underlying the placenta, termed the decidua basalis, and in the decidua parietalis (underlying the fetal chorioamniotic membranes), as well as in myometrial tissues . Such lesions are characterized by the presence of (a) fibrinoid necrosis of the vessel wall, (b) perivascular lymphocytic infiltration, and (c) accumulation of foam cells . The foam cells detected in the decidual tissues from women with acute atherosis are described as lipid‐laden macrophages; however, other non‐foamy macrophages are detected in and around these vessels.…”
Section: Introductionmentioning
confidence: 99%